Arrayed water-in-oil droplet bilayers for membrane transport analysis. Issue 16 (15th April 2016) - Watanabe, R.; Soga, N.; Hara, M.; Noji, H.
Abstract : We developed an arrayed water-in-oil droplet bilayer system for highly sensitive and quantitative membrane transport analysis. Abstract : The water-in-oil droplet bilayer is a simple and useful lipid bilayer system for membrane transport analysis. The droplet interface bilayer is readily formed by the contact of two water-in-oil droplets enwrapped by a phospholipid monolayer. However, the size of individual droplets with femtoliter volumes in a high-throughput manner is difficult to control, resulting in low sensitivity and throughput of membrane transport analysis. To overcome this drawback, in this study, we developed a novel micro-device in which a large number of droplet interface bilayers (>500) are formed at a time by using femtoliter-sized droplet arrays immobilized on a hydrophobic/hydrophilic substrate. The droplet volume was controllable from 3.5 to 350 fL by changing the hydrophobic/hydrophilic pattern on the device, allowing high-throughput analysis of membrane transport mechanisms including membrane permeability to solutes ( e.g., ions or small molecules) with or without the aid of transport proteins. Thus, this novel platform broadens the versatility of water-in-oil droplet bilayers and will pave the way for novel analytical and pharmacological applications such as drug screening.